Assessment of incidence of recurrence and constipation in patients of rectal prolapse undergoing rectal mobilization only with division of lateral stalks - Chowdhary, Devendra; Maran, Jyoti S.; Rajput, Gaurav Singh (International Surgery Journal, 2020)
Background: Rectal prolapse is a pelvic floor disorder that can occur in men and women of all ages. It results in pain, bleeding per rectum, seepage, diarrhoea or constipation and a disabled quality of life. With the advent of twentieth century, perineal operative procedures have become more common. Perineal procedures though have lower morbidities but have higher recurrence rate and high incidence of post-operative constipation. Novel abdominal approaches to rectal prolapse repair also became common during the first half of this century. Numerous types of surgical procedures have been attempted. Most techniques developed till now have some advantages and some short comings. CT Speakman and Pollen et al have shown in their studies that division of lateral ligaments caused new onset constipation and they attributed this effect to denervation of rectum. As the issue of recurrence and post-operative constipation remained unsettled. Methods: This was an observational study to assess the incidence of recurrence and post-operative constipation in patients of rectal prolapse. In well selected patients, we performed complete rectal mobilization with division of lateral ligaments. We assessed the patients on the basis of Clevland clinical constipation scoring system. Results: Out of 25 patients, 4 patients developed constipation, 2 had mild and 2 had moderate constipation and 2 patients had recurrence. Patients were kept under six monthly follow-up till a period of eighteen months. Conclusions: Only rectal mobilization with division of lateral ligaments can be a good surgical option in patients of rectal prolapse not having severe constipation.